Comparative study on two rapid and sensitive methods for quantitative determination of tenoxicam in tablets (Revista Brasileira de Ciências Farmacêuticas, 2007)
Tenoxicam, a piroxicam analogue, is an NSAID (Non-Steroid Antinflamatory Drug). It is used in the symptomatic management of musculoskeletal and joint disorders such as osteoarthritis and rheumatoid arthritis, and also in the short-term management of soft-tissue injury. Its quantitative determination in pharmaceutical formulations is important to guarantee the desired therapeutic effects. The objective of this research was to develop, validate and compare spectrophotometric and chromatographic methods in the quantitative determination of tenoxicam in tablet preparations. In this work, tablets containing 20.0 mg of tenoxicam from different origins were analyzed. The spectrophotometric method was validated using 0.1 mol/L NaOH as solvent and a signal at 368 nm was taken. The HPLC method was validated using Synergi Hydro-RP® C18 column (250x4.6 mm, 4 µm). The mobile phase was constituted of methanol-water (61:39 v/v) with pH adjusted to 2.5 with formic acid, at a flow rate of 1.0 mL/min. UV detection was made at 375 nm. All analyses were performed with a column temperature of 25 °C ± 1. The calibration curves were linear over a concentration range from 4.0-24.0 µg/mL with a correlation coefficient better than 0.9999. The detection limit (DL) and quantitation limit (QL) were 0.25 µg/mL and 0.90 µg/mL for UV method and 0.35 µg/mL and 1.20 µg/mL for HPLC method respectively. The intra-day and inter-day precision expressed as RSD were below 2% for both methods. The mean recovery of tenoxicam was found to be in the range of 98.5-101.25% for UV method and 99.01-101.93% for HPLC method. The UV and HPLC methods were found to be rapid, precise and accurate. Statistically there was no significant difference between proposed UV spectrophotometric and HPLC methods.